THE USE OF YOUTUBE AS THE SOURCE OF SUPPLEMENTARY MATERIAL IN LEARNING NEWS WRITING (Practitioner Research, 2019)
The incorporation of technology in teaching and learning has been a growing trend. Appropriate and well-managed application of technological tools in instructional activities can give great value to student learning. YouTube is a popular technological tool which can be used to enhance student learning by assisting material retention as it contains considerable videos that can be used as supplementary learning materials. This study aims to investigate the use of YouTube as the source of supplementary material in learning news writing from the perspective of students. Twenty-seven undergraduate students in the Department of Language Education and Indonesian Literature at Universitas Lambung Mangkurat were involved in this study. They were assigned to search for news videos, review and learn the content of the videos to understand the concept of news and news writing. They were then assigned to write news report using appropriate journalistic language. This study is a descriptive study that employ mix-method data analysis. A questionnaire was subsequently administered to the students to explore their perception on the use of YouTube in learning news writing. The results of data analysis revealed that the students attained benefits of using YouTube in learning news writing and completing the whole assignment. The perceived benefits include enhanced learning, comprehension on news concept, enriched knowledge, practice of learning autonomy, and assistance in developing listening as well as writing skill. It is suggested that optimal benefits of technology incorporation in teaching and learning can be achieved if teachers design activities that fit the functions offer by technological tools in accordance with the desired learning outcome.